2008
DOI: 10.1021/es8015342
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept of Desulfurization: The Electrochemically Driven and Green Conversion of SO2 to NaHSO4 in Aqueous Solution

Abstract: A new concept of desulfurization was developed by designing a series of electrochemical reactions to drive an SO2 absorption-and-conversion process in aqueous solution, hence the SO2 in gas was eventually converted to a valuable chemical of NaHSO4. A model experiment of chemically substantiating this concept includes two steps: (I) absorption of SO2 gas by aqueous solution and oxidation of the absorbed SO2 to SO4(2-) by air and (II) transformation of the SO4(2-) to NaHSO4. The experiment demonstrated that in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…, SO 4 2-, and OH -in cathodic chamber. Moreover, the final pH of cathodic chamber was 5.1-5.8 as shown in Table 1, which complied with Wang's result of 5.0-6.0 (Wang et al 2008).…”
Section: Effects Of Co 2 On Flue Gas Absorptionsupporting
confidence: 86%
See 1 more Smart Citation
“…, SO 4 2-, and OH -in cathodic chamber. Moreover, the final pH of cathodic chamber was 5.1-5.8 as shown in Table 1, which complied with Wang's result of 5.0-6.0 (Wang et al 2008).…”
Section: Effects Of Co 2 On Flue Gas Absorptionsupporting
confidence: 86%
“…In addition, a desulfurization concept (Wang et al 2008) has been developed by designing a series of electrochemical reactions to drive an SO 2 absorption and conversion process in aqueous solution. The overall reaction could be expressed as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that these aqueous solutions work well in absorbing SO 2 in the flue gas [32,33]. Compared with CaO and ZnO suspensions, Na 2 CO 3 and Na 2 SO 3 solutions can avoid the clogging problem since they are clear liquids, and more cost-effective than ZnO ones.…”
Section: Pyrolysis Process Of the Znso 3 ·25h 2 O Samplementioning
confidence: 99%
“…Conductive heating and electrolysis, two conventional but with low-efficiency methods [8][9][10], are applied to prepare NaHSO 4 crystal. However, few researches reported the NaHSO 4 crystal in regular shape by using such methods.…”
Section: Introductionmentioning
confidence: 99%